Advances in Red VCSEL Technology. (15th February 2012) - Johnson, Klein; Hibbs-Brenner, Mary; Hogan, William; Dummer, Matthew
Abstract : Red VCSELs offer the benefits of improved performance and lower power consumption for medical and industrial sensing, faster printing and scanning, and lower cost, higher speed interconnects based upon plastic optical fiber (POF). However, materials challenges make it more difficult to achieve the desired performance than at the well-developed wavelength of 850 nm. This paper will describe the state of the art of red VCSEL performance and the results of development efforts to achieve improved output power and a broader temperature range of operation. It will also provide examples of the applications of red VCSELs and the benefits they offer. In addition, the packaging flexibility offered by VCSELs, and some examples of non-Hermetic package demonstrations will be discussed. Some of the red VCSEL performance demonstrations include output power of 14 mW CW at room temperature, a record maximum temperature of115 ∘ C for CW operation at an emission wavelength of 689 nm, time to 1% failure at room temperature of approximately 200, 000 hours, lifetime in a50 ∘ C, 85% humidity environment in excess of 3500 hours, digital data rate of 3 Gbps, and peak pulsed array power of greater than 100 mW.